Simple ways to improve nutrient content and health profile in different types of foodservice products - Junkkari, Terhi; Hopia, Anu; Paakki, Maija; Mattila, Saila; Arjanne, Leena; Kantola, Maija; Luomala, Harri (Taylor & Francis, 2023)
This study shows how two foodservice products, French fries with sausage (representing vice food) and vegetable and lentil soup (representing virtue food), can be reformulated to meet the nutritional recommendations without compromising consumer acceptance. The reformulation process involved recipe development and testing, including techniques such as salt reduction, fat quality modifications, and spicing solutions to compensate the flavor changes. The reformulated products were evaluated by both consumers (N = 123) and sensory professionals (N = 9). Consumer testing revealed no significant differences in overall pleasantness between the original and the reformulated products. However, the reformulated versions received higher ratings for smell and pleasantness of appearance. This suggests that it is possible to reformulate products with conventional nutrient profiles without negatively affecting consumer acceptance. The sensory professionals also evaluated the reformulated products similarly. The nutrient content of both products significantly improved following reformulation. The study concludes by recommending the widespread implementation of reformulation techniques in the foodservice industry. Authorities are encouraged to support this by providing funding for training in recipe modification techniques. In addition, closer cooperation and knowledge sharing among stakeholders in the food supply chain are recommended to further enhance the implementation of reformulation practices.
Keywords: Reformulation; flavor profile; foodservice; recipe modification; fi=Markkinointi|en=Marketing|